The Role of Pra Calistung (Pre-Reading, Writing, and Arithmetic) Tutoring Activity in Developing Children’s Reading and Writing Skills Aged 4-6 Years - Jumaliah, Manis Lilik; Muthohar, Sofa; Fatmawati, Nilal Muna (Department of Early Childhood Education, Faculty of Education, Universitas Negeri Yogyakarta in in cooperation with in cooperation with the Perkumpulan Pengelola Jurnal PAUD (PPJ PAUD) Indonesia based on the MoU Number: 030/PPJ-PAUD/VIII/2020., 2026)
Readiness in pre-school basic literacy is a crucial foundation for academic success in elementary schools, yet many students do not have adequate preparation when the transition begins, making the urgency of early structured intervention. This research aims to describe the role of pra-calistung (pre-reading, writing, and arithmetic) tutoring activity in developing students’ reading and writing skills at Raudhatul Athfal (RA). The study used a descriptive qualitative approach with the subjects of organising tutors, group B students, and parents; the data were collected through observations, deep interviews, and documentation using observational and interviewing guidelines as the main instruments. The data was then analysed using Miles and Huberman’s model, with the steps of data reduction, data serving, and conclusion drawing. The result showed that the pra-calistung activity involving the introduction of voice, letter shapes, and articulation contributed significantly to children’s reading and writing skill enhancement, supported by the collaboration between teachers and parents. It implied that the program could become an effective and adaptive early literacy intervention model.